Combined Forward-Backward Asymmetry Measurements in Top-Antitop Quark Production at the Tevatron - Aaltonen, T.; Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Amerio, S.; Amidei, D.; et al. (Amer Physical Soc, 2018)
The CDF and D0 experiments at the Fermilab Tevatron have measured the asymmetry between yields of forward- and backward-produced top and antitop quarks based on their rapidity difference and the asymmetry between their decay leptons. These measurements use the full data sets collected in proton-antiproton collisions at a center-of-mass energy of root s = 1.96 TeV. We report the results of combinations of the inclusive asymmetries and their differential dependencies on relevant kinematic quantities. The combined inclusive asymmetry is A(FB)(t (t) over bar) = 0.128 +/- 0.025. The combined inclusive and differential asymmetries are consistent with recent standard model predictions.